HPV infection as a clinical problem - Mikołajczyk, Katarzyna; Żaba, Ryszard (Przewodnik Lekarza/Guide for GPs, 2005)
AMany serological forms of human papilloma virus are responsible for various clinical manifestations of infections caused by this virus. The HPV infection might cause diseases of the skin (verrucae planea), the mucous membranes of the mouth, digestive tract and sex organs (condyloma accuminata). In XIX century it was believed that condyloma accuminata are caused by treponema pallidum or gonorrheal infections. The viral etiology was proven in the year 1907. The use of DNA amplification with the polymerase chain reaction (PCR) found that 46% of asymptomatic college students were infected with HPV. According to current data based on undeniable scientific facts the infection with oncogenic HPV is the single most important factor in development of cervical cancer. Some of the HPV genotypes might lead to skin neoplasms. The aim of current paper was to demonstrate the variable presentations of HPV infection and to bring the attention to a possible role of those viruses in carcinogenic process.